Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1152/ajpregu.90466.2008
|View full text |Cite
|
Sign up to set email alerts
|

Histamine induces postprandial tachycardia through a direct effect on cardiac H2-receptors in pythons

Abstract: The intrinsic heart rate of most vertebrates studied, including humans, is elevated during digestion, suggesting that a nonadrenergic-noncholinergic factor contributes to the postprandial tachycardia. The regulating factor, however, remains elusive and difficult to identify. Pythons can ingest very large meals, and digestion is associated with a marked rise in metabolism that is sustained for several days. The metabolic rise causes more than a doubling of heart rate and a fourfold rise in cardiac output. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 48 publications
(62 reference statements)
6
49
1
Order By: Relevance
“…This result was evidently a postsynaptic effect, since famotidine did not affect sympathetic HA release. This result is in accordance with previous studies, in which certain H 2 receptor antagonists have been found to exhibit a cardiac protecting effect in ischemic heart diseases, including antiarrhythmia (6,7,9,34). Moreover, results in the present study confirm the mediating role of the H 2 receptor (35,36) and indicate the therapeutic potential of its antagonist in treatment of ischemia-induced ventricular arrhythmias.…”
Section: H E E T a L | M O L M E D 1 8 : 1 -9 2 0 1 2 A R R H Ysupporting
confidence: 93%
See 1 more Smart Citation
“…This result was evidently a postsynaptic effect, since famotidine did not affect sympathetic HA release. This result is in accordance with previous studies, in which certain H 2 receptor antagonists have been found to exhibit a cardiac protecting effect in ischemic heart diseases, including antiarrhythmia (6,7,9,34). Moreover, results in the present study confirm the mediating role of the H 2 receptor (35,36) and indicate the therapeutic potential of its antagonist in treatment of ischemia-induced ventricular arrhythmias.…”
Section: H E E T a L | M O L M E D 1 8 : 1 -9 2 0 1 2 A R R H Ysupporting
confidence: 93%
“…Cardiac H 2 receptors mediate positive chronotropic and inotropic effects (9,(31)(32)(33). In the present study, the selective H 2 receptor antagonist famotidine was found to slightly decrease the incidence of ischemia-induced ventricular arrhythmia and markedly reduced the duration.…”
Section: H E E T a L | M O L M E D 1 8 : 1 -9 2 0 1 2 A R R H Ysupporting
confidence: 49%
“…Pentobarbital anaesthesia does, however, mute autonomic regulation in reptiles (e.g. Crossley et al, 1998;Skals et al, 2005), and the typical withdrawal of parasympathetic tone is likely to explain the higher f H of the anaesthetized pythons than in previous studies on fully recovered pythons (Enok et al, 2012;Skovgaard et al, 2009). The lack of body movement during anaesthesia may also affect venous return, but will do so similarly in both groups and therefore have little effect on a comparison of cardiovascular parameters.…”
Section: Discussionmentioning
confidence: 92%
“…While the tachycardia stems from a combination of NANC (non-adrenergicnon-cholinergic) factors and a withdrawal of cholinergic tone (Enok et al, 2012;Skovgaard et al, 2009), the rise in V S remains more enigmatic. The postprandial increase of V S in pythons was originally ascribed to a rapid and extensive growth of the heart allowing for an elevated end-diastolic volume (Andersen et al, 2005;Secor and White, 2010), but a number of recent studies clearly demonstrate that heart mass does not increase during digestion (Hansen et al, 2013;Henriksen et al, 2014;Jensen et al, 2011;Slay et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Wood et al, 1977;Overgaard et al, 2002a;Wang and Hicks, 2008) and 30 ml min −1 kg −1 for snakes and the bearded dragon at room temperature (e.g. Skovgaard et al, 2009)] by adjusting filling pressure.…”
Section: Experimental Protocolmentioning
confidence: 99%